PENGETAHUAN MASYARAKAT TENTANG APLIKASI CEK-KLIK BPOM PADA OBAT TRADISIONAL DI KUBANG JAYA KAMPAR - Muhammad Dani Jabbar; RATNA SARI DEWI (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2021)
Public warning issued by BPOM in 2017 that 39 traditional medicines were found to contain BKO and in 2018 there were 7 traditional medicines containing BKO. One of BPOM's efforts in monitoring and protecting consumers against the circulation of unlicensed traditional medicines is by presenting the CEK Klik application on Android. This study aims to determine the level of public knowledge about the CEKklik application. This study is an observational study with a descriptive design with concurrent data collection methods through filling out online questionnaires. The research population, namely the Kubang Jaya Kampar community, amounted to 37031. The sampling technique was non-probability sampling with purposive sampling method. The number of samples was 160 respondents who met the inclusion criteria. The results showed that people who have good knowledge are 24.4%, sufficient knowledge is 47.5%, and less knowledge is 28.1%. It can be concluded that most people still do not know about the CEK CLICK application